THE STUDENTS’ PERCEPTION OF USING WHATSAPP VOICE NOTE IN LEARNING SPEAKING SKILL - Dashela, Tarina; Mustika, Yeni; Safitri, Sri Dewi Ayu; Reza, Mohammad Kamal (English Education: Jurnal Tadris Bahasa Inggris, 2025)
The purpose of this study is to figure out the students’ perspectives regarding the implementation of Whatsapp voice notes in learning speaking skills and to investigate the extent voice note contributing to the students’ speaking skills. The participants of this study were 40 students from the Information Systems Department at Bina Sarana Informatika University. The students enrolled for the English subject as basic English in the first semester of 2024. The study used qualitative data. The use of WhatsApp Voice Notes to improve speaking skills has received favorable feedback from the students. They could learn how to speak English accurately and fluently by using the voice notes on WhatsApp. Because WhatsApp voice notes allow students to learn independently at any time and from any location, they provided them with fresh experiences in speaking.